Village Device Performance in Kemusu Subdistrict - Sarsono Sarsono; Sri Wahyuni; Bambang Mursito; Supawi Pawenang (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
the performance of village officials in the kemusu of Boyolali Regency. The population in this study was all village devices in the Kemusu District Office, Boyolali Regency, which was 87 people, with the number of samples taken is 87 respondents. Based on the type of data used, this study is quantitative research. The data collection method used in this study was to distribute questionnaires to respondents to several customers who were taken as samples. The data used in this study are primary data from questionnaire answers. The data analysis techniques used in this study are statistical tests, including multiple linear regression tests, t-tests, F tests, and coefficient of determination tests. The conclusions in this study are, Leadership, organizational culture, and welfare simultaneously have a significant effect on the performance of village devices in Kemusu District, Boyolali Regency, Leadership, is the most dominant variable that affects the performance of village devices in Kemusu District, Boyolali Regency and the results of this study show that all hypotheses in this study are proven to be correct. Keywords: Performance, Leadership, organizational culture, and welfare